Corporate Response to Climate Change Mitigation: What Can We Learn From Annual Reports of European Industries? - Levihn, Fabian; Nuur, Cali; Blomgren, Henrik (International Journal of Industrial Engineering and Management, 2011)
Climate change and how best to mitigate its impact has in recent decades prefigured in the industrial development debate. Awareness about future costs related to increased atmospheric temperatures provides an incentive for lowering greenhouse gas emissions such as CO2. At the same time, measures to mitigate climate change do not only induce corporate uncertainty and pressure, but it is also provides opportunities for new businesses domains and models. The coverage of climate change issues from mass media broke with earlier trends and increased in the middle of the last decade. How about corporate focus? Was climate change issue on the corporate agenda by then? This study presents a content analysis of more than 1100 shareholder letters from 131 of the largest European public liability companies between 2000 to 2009. The main purpose of this paper is to analyze climate change from a corporate perspective. Was climate change discussed by Chief Executive Officers (CEO) and board chairmen during this time? If so, to what extent and are there industrial differences? This study shows that climate change appeared on the corporate strategic agenda in year 2005, from previously occupying a marginal place. In 2008, corporate climate change discussions were largely pushed aside by the financial crisis. It also show a trend where a shift has occurred from a general interest, towards one more divided between different industries. Article history: Received (09.06.2011); Revised (23.09.2011); Accepted (28.10.2011)